General psychological theory papers on metapsychology - Freud, Sigmund 1856-1939; Rieff, Philip 1922-2006 (New York Touchstone, 2008)
Theories on paranoia, masochism, repression, melancholia, the unconscious, the libido, and other aspects of the human psyche.
Includes bibliographical references.
Keywords: Psychology, Pathological